Report on proposed interior design scheme of Cub Prix Cafe for Safe Aim Mutual Sdn. Bhd. at Lot Pt 120962, Jalan of Raja Nazrin Shah, 31650, Ipoh, Perak. / Mohamad Idham Harun - Harun, Mohamad Idham (Faculty of Architecture, Planning and Surveying, 2011)
This final semester we are given a task either to proposed new interior design or upgrading project. I proposed a new interior design of Cub Prix Cafe for Safe Aim Mutual Sdn. Bhd. The proposed site is at Lot Pt 120962 at Ipoh, Perak. The idea of proposing a cafe is to provide a place where a fans on motorsports and customer can relax and enjoy the games at the same time. This project was followed by a few stages of progress. Every stages is include with presentation. The stages goes by proposal stage then followed by planning stage and lastly final presentation. The project is completed when all this stages is complete.